Assessment of the strength of the pelvic floor musculature in women who practice Mat Pilates. - Diniz, Marklana da Frota; Vasconcelos, Thiago Brasileiro de; Pires, Juliana Lerche Vieira Rocha; Nogueira, Marineide Meireles; Arcanjo, Giselle Notini (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The Pilates Method is a program of physical and mental training that works the body as a whole, aiming to gain muscle strength, mainly at the central region formed by the abdominal muscles, spine and pelvic floor, and to promote stretching and flexibility. Objective: To investigate the effects of this technique in the pelvic floor muscle activity, noting the type of fiber was more work during the practice of this activity in soil (Mat Pilates). Methodology: It was a character study of interventional, observational, descriptive, conducted during the months from March to May 2011, in which six women aged between 35 and 65 years, who underwent Mat Pilates classes twice a week, was rated the strength of pelvic floor, by Perina® perineometer pressure before and after eight classes. Results: It was observed that all the volunteers had increased the muscle strength in both types of muscle fibers, and 84% (p < 0.05) had greater gain in Type 2 fibers. Conclusion: The Mat Pilates influences in the increase of the pelvic floor muscle strength it and can be used to prevent dysfunction of these muscles.